2008
DOI: 10.1016/j.ydbio.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Higher order chromatin structure at the X-inactivation center via looping DNA

Abstract: In mammals, the silencing step of the X-chromosome inactivation (XCI) process is initiated by the non-coding Xist RNA. Xist is known to be controlled by the non-coding Xite and Tsix loci, but the mechanisms by which Tsix and Xite regulate Xist are yet to be fully elucidated. Here, we examine the role of higher order chromatin structure across the 100-kb region of the mouse X-inactivation center (Xic) and map domains of specialized chromatin in vivo. By hypersensitive site mapping and chromosome conformation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 53 publications
3
75
1
1
Order By: Relevance
“…By contrast, the 81-bp RS14d has 86% identity between mouse and human sequences and 80% identity between mouse and bovine sequences. RS14d coincides with a strong DNase I hypersensitive site (Tsai et al 2008).…”
Section: Computational Analysis Identifies a Conserved Element Rs14mentioning
confidence: 95%
See 4 more Smart Citations
“…By contrast, the 81-bp RS14d has 86% identity between mouse and human sequences and 80% identity between mouse and bovine sequences. RS14d coincides with a strong DNase I hypersensitive site (Tsai et al 2008).…”
Section: Computational Analysis Identifies a Conserved Element Rs14mentioning
confidence: 95%
“…It was also shown that ACH-1 and ACH-2 are separated by a chromatin transitional zone located at the 39 terminus of Xist ( Figure 1A) (Tsai et al 2008), which was proposed to buffer opposing chromatin forces between the Tsix-and the Xist-centered domains. How this region does so is not known, but the 39 end of Xist has a number of noteworthy features, including a strong DNase I hypersensitive site (Tsai et al 2008).…”
mentioning
confidence: 99%
See 3 more Smart Citations